Wearable Conformal Antennas for 2.4 GHz Wireless Body Area Networks - Emad Shehab Ahmed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Microstrip fed inset patch antennas embedded in planar and cylindrically curved surfaces are introduced to be used in Body Area Networks (BANs) presented. These antennas are designed as wearable antennas for industrial, scientific and medical (ISM) band wireless communication networking. The proposed antennas consist of 50 Ω microstrip line feeding inset patch printed on the front face of dielectric substrate and a rectangular ground plane on the bottom face. The proposed planar antenna is conformed on finite cylindrical substrates of radii 2.5, 5 and 7.5 cm corresponding approximately to the typical size of human wrist, humerus and shoulder of a human body respectively. Modeling and performance evaluation of the cylindrical structures has been carried out using the commercially available electromagnetic software CST Studio Suite2009. Simulation results, obtained for the return losses, current distribution, and radiation pattern of the antennas are presented. Furthermore, results show that the designed conformal antennas are resonating at the designed frequency with reasonable gain and field pattern characteristics.